2011
DOI: 10.1089/dna.2010.1164
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Single-Nucleotide Polymorphisms in Pre-miRNAs and the Risk of Asthma in a Chinese Population

Abstract: Single-nucleotide polymorphisms (SNPs) in pre-miRNAs may alter microRNA (miRNA) expression levels or processing and contribute to susceptibility to a wide range of diseases. We investigated the correlation between four SNPs (rs11614913, rs3746444, rs2910164, and rs229283) in pre-miRNAs and the risk of asthma in 220 asthma patients and 540 controls using polymerase chain reaction-restriction fragment length polymorphism methodology and DNA-sequencing. There were significant differences in the genotype and allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 29 publications
1
23
0
1
Order By: Relevance
“…The GG genotype was associated with reduced risk of asthma in children born to asthmatic mother, whereas the GG genotype was associated with increased risk of asthma in children born to nonasthmatic mothers. In another study, SNPs in pre-miRNA sequence (miR-146a rs2910164 and miR-149 rs2292832) were associated with a reduced risk of asthma in a Chinese population [94]. …”
Section: Mirnas and Asthmamentioning
confidence: 99%
“…The GG genotype was associated with reduced risk of asthma in children born to asthmatic mother, whereas the GG genotype was associated with increased risk of asthma in children born to nonasthmatic mothers. In another study, SNPs in pre-miRNA sequence (miR-146a rs2910164 and miR-149 rs2292832) were associated with a reduced risk of asthma in a Chinese population [94]. …”
Section: Mirnas and Asthmamentioning
confidence: 99%
“…The C allele of the rs2910164 G>C polymorphism of miR-146a causes mis-pairing within the miR-146a hairpin, decreased expression of its mature form, and abated expression of its target genes, including TNF receptor-associated factor 6 (TRAF6) and IL-1 receptor-associated kinase 1 (IRAK1) [15]. This functional polymorphism was most extensively studied for its association with various diseases, including temporal lobe epilepsy [16], asthma [17], SLE [9,18], and RA [10]. A very recent study also demonstrated that the rs57095329 A>G polymorphism in the promoter region of miR-146a was associated with SLE in Chinese individuals, and the mutant allele alleviated miR-146a expression through the reduction of its binding affinity for the transcription factor Ets-1 [18].…”
Section: Introductionmentioning
confidence: 99%
“…In a case-control study for risk factor for asthma, SNPs demonstrated risk variant rs2910164*C allele (C/G) in the pre-miRNA of miR-146a and rs2292832*T (C/T) miR-149 were significantly associated with lower risk of asthma [12] (Table 1). Corroborating the finding, Jimenez-Morales et al reported rs2910164*C (G/C) miR-146a to be significantly associated with protection against asthma among Mexican females [13].…”
Section: Introductionmentioning
confidence: 99%